An Effective Pain Management with Peanut Ball and Aromatheapy Rose for Pain Reduction at the Time of Childbirth - Tambunan, Lensi Natalia; Trihartiningsih, Evie (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2023)
The delivery process, pain is regarded as the most unpleasant even the most chilling by mothers. The pain can affect the condition of the mother is a tired, fear, worry, and stress. Handling pain in non-pharmacological in pregnancy and childbirth is a method of relaxation are cheaper, effective, simple and without side effects as using peanut ball and aromatherapy rose. This study aims to know the effect of peanut ball and aromatheapy rose in the reduction of pain during childbirth. The method used in this study is literature review by examining a number of articles that have been determined, this study consists of 10 articles that will be analyzed with the technique of manual article selection. It has been discovered that the use of peanut balls and the giving of aromatheapys has an effect on poenurunan birth pain when phase I. It is expected that use peanut ball and the provision of aromatherapy rose as a way of an alternative aimed at reducing pain in childbirth when Phase I.